Analysis of Various Methods in Learning, Memorizing and Translating the Qur'an - Syaifuddin Sabda; Ani Cahyadi; Firdaus, Firdaus (Universitas Muhammadiyah Sidoarjo, 2023)
The process of memorizing and translating the Quran is essential for Muslims to understand and practice the teachings of the religion. Memorizing the Quran can be done through various methods, such as individual or group memorization, using technology, or with the guidance of a teacher. Translating the Quran is also essential for understanding the meaning of the verses in a more easily understood language. There are several approaches to solving the Quran, such as translating verse by verse or using commentary to understand the context of the verse. Both processes are ways to enhance understanding and implementation of the teachings of the Quran in daily life.